2019
DOI: 10.1360/n032018-00203
|View full text |Cite
|
Sign up to set email alerts
|

Construction and manipulation of self-assemble structures on solid surfaces

Abstract: Construction of two-dimensional (2D) molecular crystals on solid surfaces is an important way to synthesize supermolecular materials and functionalize solid surfaces. In this review, we provide an overview of the formation mechanism of the 2D self-assembled molecular crystals, and the control of the structures and electronic structures by combining theoretical calculations with scanning tunneling microscopy (STM). Here we focus on the molecular selfassembled structures dominated by weak interactions. Several k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…With the progress of advanced surface analysis techniques including high-resolution scanning tunneling microscopy (STM), it is possible to reveal chiral phenomena like chiral recognition and transformation in on-surface reactions at the single molecular level. Such chiral studies on surfaces also provide deep insights into heterogeneous asymmetric catalysis, chiral separation, chiral sensing, etc. , Another impetus in investigating chiral on-surface reactions comes from the fabrication and property investigation of chiral species, including chiral molecules and low-dimensional chiral nanostructures. As an innovative approach for the growth of low-dimensional nanostructures and materials, on-surface synthesis is promising for the fabrication of novel chiral species with unusual physical and chemical properties, especially those that are not readily accessible under wet chemistry. One example of such chiral species is chiral graphene nanoribbons. It has been demonstrated that chiral graphene nanoribbons exhibit unique one-dimensional edge states with an unusual magnetic structure. , Furthermore, the structure of the product generated via on-surface synthesis can be finely tuned and unambiguously determined with atomic precision, paving the way for studying the intrinsic physical and chemical properties of chiral species and elucidating their structure–property correlation at the single molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of advanced surface analysis techniques including high-resolution scanning tunneling microscopy (STM), it is possible to reveal chiral phenomena like chiral recognition and transformation in on-surface reactions at the single molecular level. Such chiral studies on surfaces also provide deep insights into heterogeneous asymmetric catalysis, chiral separation, chiral sensing, etc. , Another impetus in investigating chiral on-surface reactions comes from the fabrication and property investigation of chiral species, including chiral molecules and low-dimensional chiral nanostructures. As an innovative approach for the growth of low-dimensional nanostructures and materials, on-surface synthesis is promising for the fabrication of novel chiral species with unusual physical and chemical properties, especially those that are not readily accessible under wet chemistry. One example of such chiral species is chiral graphene nanoribbons. It has been demonstrated that chiral graphene nanoribbons exhibit unique one-dimensional edge states with an unusual magnetic structure. , Furthermore, the structure of the product generated via on-surface synthesis can be finely tuned and unambiguously determined with atomic precision, paving the way for studying the intrinsic physical and chemical properties of chiral species and elucidating their structure–property correlation at the single molecular level.…”
Section: Introductionmentioning
confidence: 99%